2022
DOI: 10.1109/access.2022.3190373
|View full text |Cite
|
Sign up to set email alerts
|

Organisational Privacy Culture and Climate: A Scoping Review

Abstract: New regulations worldwide are increasingly pressing organisations to review how they collect and process personal data to ensure the protection of individual privacy rights. This organisational transformation involves implementing several privacy practices (e.g., privacy policies, governance frameworks, and privacy-by-design methods) across multiple departments. The literature points to a strong influence of the organisations' culture and climate in implementing such privacy practices, depending on how leaders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…It is also worth mentioning that six out of the ten studies in the related work (see Table 1) are country-specific, i.e., in which all the interviewed participants live in the same country. The importance of including more diverse populations and independently replicating prominent studies has already been stressed in the literature, such as the scoping review on OPCC [43]. For such reasons, our research contributes to the existing body of evidence, corroborating and introducing new findings.…”
Section: Identified Research Gapsmentioning
confidence: 52%
See 2 more Smart Citations
“…It is also worth mentioning that six out of the ten studies in the related work (see Table 1) are country-specific, i.e., in which all the interviewed participants live in the same country. The importance of including more diverse populations and independently replicating prominent studies has already been stressed in the literature, such as the scoping review on OPCC [43]. For such reasons, our research contributes to the existing body of evidence, corroborating and introducing new findings.…”
Section: Identified Research Gapsmentioning
confidence: 52%
“…Scholars have also turned to large software repositories (e.g., GitHub and Stack Overflow), mining posts and question-and-answer websites to interpret how developers talk about privacy [40], [41]. Lastly, secondary research, in the forms of systematic reviews, has also been able to synthesise this growing body of evidence on factors affecting the implementation of privacy and security practices [42] and the conceptualisation of emerging topics such as Organisational Privacy Culture and Climate (OPCC) [43].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Case studies are shown to be one of the most common methodologies for evaluation; nonetheless, other methodologies could be considered, such as using grounded theory in the context of socio-technical systems [96]. This need for further evaluation research has also been discussed in the broader area of privacy engineering [14], [97].…”
Section: B Research Directions 1) Evaluation Researchmentioning
confidence: 99%
“…Scholars have also turned to large software repositories (e.g., GitHub and Stack Overflow), mining posts and question-and-answer websites to interpret how developers talk about privacy [57], [58]. Lastly, secondary research, in the forms of systematic reviews, has also been able to synthesise this growing body of evidence on factors affecting the implementation of privacy and security practices [59] and the conceptualisation of emerging topics such as Organisational Privacy Culture and Climate (OPCC) [60].…”
Section: Related Workmentioning
confidence: 99%